Persepsi Masyarakat Terhadap Rencana Pembangunan Ekowisata Karst Di Desa Sambueja, Kecamatan Simbang, Kabupaten Maros - Asar Said Mahbub; Andi Wahyunira; Amran Achmad (PERENNIAL, 2018)
Sambueja Village is one of the villages in Maros Regency which has a karst area that must be protected in total because its function as a water storage and has a variety of ecotourism potential that can be developed and can support the development of ecotourism activities. The role and participation of the community in ecotourism is an important thing that distinguishes it from other forms of tourism. Because perception is a fundamental element that needs to be known before planning activities that will involve the local community. This study aims to determine the public perception of the karst ecotourism development plan in Sambueja Village, Simbang District, Maros Regency. The results of the study can be seen that the perception of the people of Sambueja Village is a positive perception of the karst ecotourism development plan. The majority of the community stated that they did not object if the village of Sambueja was built and developed as an ecotourism village, but it requires that its development and development must refer to the concept of tourism which takes into account the preservation of environmental functions, ecological potential and maintaining cultural values in the local communityKey words: Sosial Perception; Karst Ecotourism